Vitamin D receptor polymorphisms and the susceptibility of Parkinson's disease. (23rd April 2019) - Wang, Xiong; Shen, Na; Lu, Yanjun; Tan, Kun
Highlights: VDR rs2228570 polymorphism was associated with PD in Asian population. VDR rs2228570 polymorphism was not associated with PD in Caucasian population. VDR rs1544410 polymorphism was not associated with PD. Abstract: Epidemiological evidence concerning the association between vitamin D receptor (VDR) polymorphisms, including rs2228570, rs731236, rs7975232, rs1544410 and Parkinson's disease (PD) risk is inconsistent. A meta-analysis was performed to evaluate these associations via searching PubMed and EMBASE databases up to Jan 4, 2019. Odds ratio (OR) with 95% confidence interval (CI) were applied to assess the strength of these associations. 6 studies with 1391 PD cases and 1570 controls for rs2228570, 7 studies with 1881 PD cases and 2135 controls for rs731236, 5 studies with 1298 PD cases and 1536 controls for rs7975232, and 6 studies with 932 PD cases and 1377 controls for rs1544410 were included in this meta-analysis. Significant associations between rs2228570 and PD risk were found in allelic, dominant, and additive models but not in recessive model. Stratified study revealed that rs2228570 was associated with PD susceptibility in Asian population, while no significant association was observed in Caucasian population. Sensitivity analysis showed stable results for rs2228570 and no publication bias existed. Rs731236 was associated with increased PD risk in dominant model, however, this result was unstable. No significant association was found between rs7975232 or rs1544410 and PD.